2005
DOI: 10.1097/00152193-200508001-00002
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying biphasic defibrillation

Abstract: This technology is making defibrillators less likely to injure patients. Here's what you need to know.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This reduces the potentially adverse effect of patient impedance on successful defibrillation. 11 Another recent development in defibrillators is the degree to which the device can make decisions regarding the diagnosis and treatment of the arrhythmia. Auto mated external defibrillators (AEDs), are designed to assist individuals with minimal training perform CPR, defibrillation, and cardioversion in people.…”
Section: Defibrillation and Cardioversionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduces the potentially adverse effect of patient impedance on successful defibrillation. 11 Another recent development in defibrillators is the degree to which the device can make decisions regarding the diagnosis and treatment of the arrhythmia. Auto mated external defibrillators (AEDs), are designed to assist individuals with minimal training perform CPR, defibrillation, and cardioversion in people.…”
Section: Defibrillation and Cardioversionmentioning
confidence: 99%
“…The rectilinear waveform maintains a stable shape in response to impedance, and the constant current in the first phase reduces potentially harmful peak currents. 11 The truncated exponential biphasic (TEB) waveform was developed for internal use in implantable cardioverterdefibrillators (ICDs), where impedance is generally low relative to external methods. If a TEB waveform is utilized in an external defibrillationcardioversion attempt, then thoracic impedance may alter the waveform's shape.…”
Section: Safety Issuesmentioning
confidence: 99%
“…Atrial arrhythmias are common after cardiac surgery 8. The incidence of atrial arrhythmias has been reported to be 10–65% after cardiac surgery 10.…”
Section: Introductionmentioning
confidence: 99%